Internal audits as a tool to assess the compliance with biosecurity rules in a veterinary faculty - Humblet, Marie-France; Saegerman, Claude (Frontiers in Veterinary Science, 2023)
Introduction The present paper proposes a tool to follow up the compliance of staff and students with biosecurity rules, as enforced in a veterinary faculty, i.e., animal clinics, teaching laboratories, dissection rooms, and educational pig herd and farm. Methods Starting from a generic list of items gathered into several categories (personal dress and equipment, animal-related items, infrastructures, waste management, management of material/equipment and behavior), a checklist was created for each sector/activity mentioned above, based on the rules and procedures compiled in the Faculty biosecurity standard operating procedures. Checklists were created as Excel™ files. For each sector, several sheets were elaborated, i.e., one per specific activity: for example, the following sheets were created for the equine clinic: class 1-2 hospitalization (class 1 = non-infectious conditions; class 2 = infectious disease with a low or non-existent risk of transmission), class 3 hospitalization (class 3 = infectious disease with a moderate risk of transmission; these patients are suspected of having an infectious disease and being contagious for other patients and/or for humans) and consultation. Results Class 4 area, which corresponds to the isolation unit and aims at housing patients suffering from infectious diseases with a significant risk of transmission (including notifiable conditions), was not audited at that period, as it was undergoing renovation works. The audit relied on observations performed by a unique observer to ensure standardization. Observed items were presented as yes/no and multiple-choice questions. A scale from 0 to 3 or 4 (depending on the item) allowed scoring each item, i.e., 0 corresponding to 100% compliance with the procedure and the highest score to the worst situation. A median and average global score was also estimated by category and by activity. Discussion The methodology described in the present paper allows estimating the compliance with biosecurity standard operating procedures in a specific sector and/or for a given activity. The identification of criteria needing improvement is a key point: it helps prioritizing actions to be implemented and awareness raising among people concerned. Regular internal auditing is an essential part of a biosecurity plan, the frequency being conditioned by the risk linked to a specific activity or area (i.e., more frequent audits in risky situations).